Birthweights of infants born before 30 weeks' gestation. Issue 12 (December 1984) - Brooke, O G; McIntosh, N
Abstract : We give birthweight data with centiles on 222 singleton infants born between 24 and 30 weeks' gestation at St George's Hospital, London.